2006
DOI: 10.5194/hess-10-575-2006
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and simulation of nutrient retention and management for a lowland river-lake system

Abstract: Abstract. In the context of the European Water Framework Directive, we studied the possible impact of reduced emissions on phosphorus and nitrogen concentrations in a lowland river-lake system (Havel River, Germany). As a prerequisite, we quantified the retention of nutrients in the river from mass balances and deduced its seasonal variation. We detected that about 30% of the total nitrogen input is retained within the surveyed river section. In contrast, phosphorus release from sediments was shown to cause a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…Both TN and NH 3 -N reached their peaks in winter, valleys in summer. Similarity phenomenon was observed in other RLCSs [24] and lakes [14], which may be attributed to the high efficiency of denitrification in high-temp seasons. But TN always reached its peaks two months earlier than that of NH 3 -N. These results suggested that organic nitrogen transformed into NH 3 -N during this period.…”
Section: Spatial and Seasonal Variations Of Variable Patternssupporting
confidence: 61%
“…Both TN and NH 3 -N reached their peaks in winter, valleys in summer. Similarity phenomenon was observed in other RLCSs [24] and lakes [14], which may be attributed to the high efficiency of denitrification in high-temp seasons. But TN always reached its peaks two months earlier than that of NH 3 -N. These results suggested that organic nitrogen transformed into NH 3 -N during this period.…”
Section: Spatial and Seasonal Variations Of Variable Patternssupporting
confidence: 61%
“…A high P release potential was already found by Kneis et al (2006) for other downstream Havel River lakes. Fig.…”
Section: Scenarios Resultsmentioning
confidence: 69%
“…The use of a hydrodynamic model able to simulate transport and mixing in waterbodies is here important because these processes can influence strongly the dynamics of eutrophication (Lindim et al, 2011). The inclusion of a benthic module to predict the contribution of diagenetical processes is of major importance to simulate water quality in the Lower Havel since phosphorus internal loads have been found to be a main contributor to water column nutrient levels (Kneis et al, 2006).…”
Section: Models Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes water quality simulation (Kneis et al, 2006(Kneis et al, , 2009, flood retention modeling (F€ orster et al, 2005), and runoff forecasting (Kneis et al, 2012). At a certain level of abstraction, the specific model engines used in the cited studies were actually identical.…”
Section: Background and Objectivesmentioning
confidence: 99%